IMPROVING SCIENCE LEARNING OUTCOMES THROUGH OUTDOOR STUDY AT SD 46 LUBUKLINGGAU - putri Veronika (CV Grasta Glory, 2026)
Low science learning outcomes among elementary school students indicate the need for learning models that actively engage students and utilize real learning environments. This study aims to determine whether the Outdoor Study learning model can improve science learning outcomes of fourth-grade elementary school students at SDN 46 Lubuklinggau. This study employed an experimental research design with 20 fourth-grade students as research subjects, consisting of 12 boys and 8 girls. The learning model applied was the Outdoor Study model. Data were collected through tests, observations, and documentation, and analyzed using descriptive qualitative and descriptive quantitative techniques. The research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The results showed an improvement in students’ science learning outcomes. In Cycle I, the average pre-test score was 54.25 and increased to 61.50 in the post-test. In Cycle II, the average pre-test score improved to 64.75 and further increased to 75.25 in the post-test. These findings indicate that the Outdoor Study learning model effectively enhances students’ science learning outcomes. In conclusion, the Outdoor Study model can be used as an alternative learning approach to improve science achievement at the elementary level. This study implies that teachers are encouraged to integrate outdoor learning activities into science instruction, and future research is recommended to apply this model to other subjects or larger samples to strengthen its effectiveness.